(untitled) (Trabalho & Educação, 2017)
This article discusses the offering of right to education to individuals deprived of their liberty in the state of Pará, the processes of work and training of teachers and education professionals who are daily involved with the guarantee of basic education in prison units, it sought to problematize the determinants and challenges of teaching work in the area, and think about the alternatives that are being implemented in particular from the Curso de Especialização em Educação de Jovens e Adultos Privados de Liberdade (Specialization Course in Youth and Adult Education Deprived of Freedom), held between in 2015-2016, by the Universidade Federal do Pará (Federal University of Pará). The text deals with the structural determinants of education in prisons in Pará and their unfolding in relation to teaching work, considering documentary analysis and bibliographical review produced throughout the teachers training process, pointing out questions from the perspective of those who work directly in the classrooms of the prisons of Pará, and which are included in the monographs defended at the end of the Course, aiming to capture the analysis and propositions of educators and other individuals who have concrete insertion in the places of deprivation of liberty. ___ O presente artigo aborda a oferta do direito à educação às pessoas privadas de liberdade no estado do Pará e os processos de trabalho e de formação de professores e profissionais da educação que se envolvem cotidianamente com a garantia da educação básica em unidades prisionais. Procurou-se problematizar os condicionantes e os desafios do trabalho docente na área, além de refletir sobre as alternativas que vêm sendo executadas, em especial, a partir do Curso de Especialização em Educação de Jovens e Adultos Privados de Liberdade, realizado entre 2015 e 2016 pela Universidade Federal do Pará. O texto aborda os condicionantes estruturais da educação em unidades prisionais no Pará e os s eus desdobramentos em relação ao trabalho docente, a partir de análise documental e revisão bibliográfica realizada ao longo do processo de formação dos docentes, procurando apontar questões a partir do olhar daqueles que atuam diretamente nas salas de aula das unidades prisionais paraenses e que constam das monografias defendidas no fim do curso, com o sentido de captar as análises e as proposições de educadores e outros sujeitos que têm inserção concreta nos espaços de privação de liberdade.